Practical Synthesis of 1,2,3,4-Tetrahydroisoquinoline-1-phosphonic and -1-phosphinic Acids through Kabachnik–Fields and Aza-Pudovik Reaction - Hernández-Moreno, Jesús Tadeo; Romero-Estudillo, Ivan; Cativiela, Carlos; Ordóñez, Mario (Synthesis, 2020)
We report here an alternative and practical method for the preparation of 1,2,3,4-tetrahydroisoquinoline-1-phosphonic acid and the first synthesis of 1,2,3,4-tetrahydroisoquinoline-1-H-phosphinic and 1,2,3,4-tetrahydroisoquinoline-1-phenylphosphinic acids through Kabachnik–Fields and aza-Pudovik reaction. This methodology does not require any metallic catalyst and proceeds under mild reaction conditions.
Keywords: α-aminophosphonic acids; α-aminophosphinic acids; N-acyliminium ions; Kabachnik–Fields reaction; aza-Pudovik reaction